Role of Cloud Computing & Artificial Intelligence in the Logistics & Supply Chain Industry - Sornprom, Natapong (Transactions on Engineering and Computing Sciences, 2024)
The logistics and supply chain sector finds itself at a critical inflexion point, with mounting pressures to enhance efficiency, increase cost competitiveness and serve the dynamic needs of consumers. To aid such goals, technologies of cloud computing combined with artificial intelligence (AI) come into play. Scalable resources, real-time data access (SaaS), and collaboration offer a superior environment for consolidation, better communication between departments and resource integration across business operations. Further, AI with sophisticated techniques of machine learning have ability to analyze large data sets which enables businesses to automate certain tasks while minimizing certain operations apart from providing predictions. This paper dwells on how cloud computing combined with AI can help in transformation of logistics supply chain management. How businesses across the verticals are leveraging these technologies to improve operations and providing a beacon for technological advancements in their growth. Furthermore, how cloud and AI integration can help industry and gain competitive edge in a rapidly evolving market to foster a more agile, resilient customer centric ecosystem. By adopting such technologies, businesses can navigate through the complexities of modern logistics and supply chain challenges and stay relevant in this hyper competitive digital landscape.